Does complex PTSD predict or moderate treatment outcomes of three variants of exposure therapy?. (May 2021) - Hoeboer, Chris M.; de Kleine, Rianne A.; Oprel, Danielle A.C.; Schoorl, Maartje; van der Does, Willem; van Minnen, Agnes
Highlights: Complex PTSD is related to more severe PTSD and comorbidity at baseline. Complex PTSD does not predict treatment outcome of variants of Prolonged Exposure. Complex PTSD is not related to better outcome of STAIR + PE compared to PE and iPE. Abstract: Background: One reason for the inclusion of Complex Posttraumatic Stress Disorder (CPTSD) in the 11th revision of the International Classification of Diseases (ICD-11) was its suspected relevance for treatment indications. We investigated whether CPTSD predicted and moderated treatment outcomes of Prolonged Exposure (PE), intensified PE (iPE) and Skills Training in Affective and Interpersonal Regulation followed by PE (STAIR + PE). We expected that CPTSD would predict worse treatment outcomes across treatments. Secondly, we expected that CPTSD would lead to better treatment effect in STAIR + PE compared to PE and iPE. Methods: We analyzed 149 patients with childhood-abuse related PTSD from a randomized clinical trial. CPTSD diagnosis and symptom severity were measured with the International Trauma Questionnaire. The main outcome was change in clinician-assessed PTSD symptoms. Assessments took place at baseline, week 4, week 8, week 16 (post-treatment) and at a 6-and 12-month follow-up. Analyses were based on an intention-to-treat sample using mixed effect models. Results: More than half (54 %) of the patients met criteria for CPTSD at baseline. CPTSD was related to more severe PTSD symptoms and higher comorbidity at baseline. CPTSD neither predicted nor moderated treatment outcome. Limitations: Inclusion was limited to patients with PTSD related to childhood abuse. Replication is needed in different samples. Conclusions: CPTSD is associated with more severe PTSD and with higher comorbidity. CPTSD did not predict treatment outcome and did not indicate differential treatment outcome of STAIR + PE compared to PE and iPE.